LSPR Biosensor Based on Nanostructured Gold Films: Detection of Mycotoxins. (2017) - Al-Rubaye, Ali Ghamin; Nabok, Alexei; Tsargorodska, Anna
Abstract: This work focuses on the development of optical sensors based on the LSPR phenomenon in nano-structured gold films suitable for detection of mycotoxins. A simple technology of annealing thin gold films was utilized for the formation of gold nano-islands exhibiting the LSPR effect. The morphology of gold nano-structures produced was studied with SEM and AFM while their optical properties were analysed with UV-vis absorption spectroscopy and spectroscopic ellipsometry (SE). A blue spectral shift of LSPR band caused by changes in the refractive index of medium constitutes the main principle of LSPR sensing. Bio-sensing tests were attempted using SE in total internal reflection mode (TIRE); a noticeable spectral shift was recorded on course of immune binding of aflatoxin B1 to specific antibodies immobilized on the surface of gold.